Revisiting the Calculation Debate: A Call for a Multiscale Approach. Issue 2 (3rd April 2022) - Adaman, Fikret; Devine, Pat
Abstract : This essay provides a framework to develop policies that can both resist the capitalist system and formulate alternatives to it, by critically reviewing discussions of an ecosocialist society and its economic organization through revisiting the "calculation debate" that was started in the 1930s and is still ongoing. It underlines the importance of repoliticizing the economic sphere to reembed the economy in society rather than society being subordinated to the economy. To that aim, it emphasizes the gravity of (1) planning our future, (2) coordinating our decisions before we embark on any action, (3) relying on knowledge in different forms and formats as articulated at both the individual and societal level, and (4) generating real democracy via participatory and deliberative mechanisms. Finally, the essay critically assesses progressive responses to current economic, ecological, and health crises and, because local and macro initiatives are equally important and feed one another positively, advocates for adopting a multiscale approach.